REVIEW OF THE BOOK "ATHLETES’ LIFE SATISFACTION AND SATISFACTION WITH SOME ASPECTS OF LIFE - Stoyanova, Stanislava (Psychological thought, 2025)
A book review is presented regarding the book by Nikolay Ivantchev, PhD, focused on athletes’ satisfaction of different aspects of life, as well as their general life-satisfaction. This monograph is in the area of Sport Psychology, but it would be interesting to a broad audience.